1991
DOI: 10.1159/000174861
|View full text |Cite
|
Sign up to set email alerts
|

Relative Prognostic Value of Clinical Heart Failure and Early Echocardiographic Parameters in Acute Myocardial Infarction

Abstract: The relative prognostic value of clinical heart failure and early M-mode and 2-dimensional echocardiographic indexes of left ventricular performance was compared in a study of 205 consecutive patients with acute myocardial infarction (AMI). Statistical analysis showed that an early wall motion score was a stronger predictor of 1 -year mortality than the occurrence of clinical heart failure early, late or at any time during the hospital course of AMI. The finding of clinical heart failure had an independent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…A 95% confidence interval for a single determination of LVEF of ± 16 LVEF units ( ± 0.16) is comparable with the results of previously published more elaborate échocardio graphie methods [32,33]. Despite the relative lack of accuracy of wall motion index and of the proposed wall motion derived estimate of LVEF, these indices neverthe less appear sufficiently accurate to contribute to the solu tion of clinical problems [4,34,35]. It is possible that a closer approximation of linearity could be obtained by giving wall motion scores from different segments differ ent weight in the index as suggested by Rifkin et al [27] and Rifkin and Koito [28]; however at the cost of increased complexity.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…A 95% confidence interval for a single determination of LVEF of ± 16 LVEF units ( ± 0.16) is comparable with the results of previously published more elaborate échocardio graphie methods [32,33]. Despite the relative lack of accuracy of wall motion index and of the proposed wall motion derived estimate of LVEF, these indices neverthe less appear sufficiently accurate to contribute to the solu tion of clinical problems [4,34,35]. It is possible that a closer approximation of linearity could be obtained by giving wall motion scores from different segments differ ent weight in the index as suggested by Rifkin et al [27] and Rifkin and Koito [28]; however at the cost of increased complexity.…”
supporting
confidence: 79%
“…The reproducibility of wall motion index was not examined in this study, but a low interob server variability has previously been shown [4,30], Finally, it should be kept in mind that part of the described imprecision may be due to the fact that the radionuclide reference method used in this study -for the purpose of comparison -was defined as giving a true LVEF which is not quite the case. Also, it could be argued that the echo parameters contain physiological and prog nostic information in themselves, quite independent of their correlation with radionuclide LVEF [30,31,34].…”
mentioning
confidence: 99%
“…6,7 Moreover, measurements of cardiac performance, such as left ventricular ejection fraction and wall motion index, have an important impact on the prognosis. 8,9 Levels of natriuretic peptides have been shown to reflect cardiac per-formance. This review focuses on the emerging role of these peptides in the early risk stratification of unstable CAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Vasodilating properties or partial agonist activity have been suggested to reduce some of the negative inotropic or chronotropic effects of ,B receptor antagonists, although concerns have been raised that the agonist activity could abolish the beneficial effect on mortality especially after myocardial infarction. "1 Xamoterol, a /3, receptor antagonist with high partial agonist activity improves symptoms and exercise tolerance in patients with mild to moderate chronic heart failure'2 without deleterious effects on prognosis, 3 although doubts have been raised in severe heart failure. '4 The effect of xamoterol on exercise tolerance was superior to that of digitalis.…”
mentioning
confidence: 99%